Semi-Solid and Solid Dosage Forms for the Delivery of Phage Therapy to Epithelia - Teagan L. Brown; Steve Petrovski; Hiu Tat Chan; Michael J. Angove; Joseph Tucci (MDPI AG, 2018)
The delivery of phages to epithelial surfaces for therapeutic outcomes is a realistic proposal, and indeed one which is being currently tested in clinical trials. This paper reviews some of the known research on formulation of phages into semi-solid dosage forms such as creams, ointments and pastes, as well as solid dosage forms such as troches (or lozenges and pastilles) and suppositories/pessaries, for delivery to the epithelia. The efficacy and stability of these phage formulations is discussed, with a focus on selection of optimal semi-solid bases for phage delivery. Issues such as the need for standardisation of techniques for formulation as well as for assessment of efficacy are highlighted. These are important when trying to compare results from a range of experiments and across different delivery bases.